Reactive Adjustment or Proactive Embedding? Multistudy, Multiwave Evidence for Dual Pathways to Expatriate Retention. Issue 1 (17th May 2013) - Ren, Hong; Shaffer, Margaret A.; Harrison, David A.; Fu, Carmen; Fodchuk, Katherine M.
<x xml:space="preserve">Abstract</x> The dominant perspective on expatriation characterizes the process as a continuing adaptation to existing job demands on an international assignment. Another, less studied perspective, emphasizes that expatriates can initiate tactics to acquire task, interpersonal, and affective resources for shaping their assignment experiences. Adopting a positive organizational scholarship lens and drawing on the job demands–resources model, we simultaneously examine both of these reactive demand‐based and proactive resource‐based pathways to expatriate retention. We propose that cross‐cultural uncertainty demands and expatriate‐initiated resource acquisition tactics both influence adjustment and embeddedness. Thus embeddedness works alongside adjustment to drive expatriates' plans to remain in the international position, which in turn leads to actual retention. Using evidence from 2 separate panel studies (one with 2 waves and the other with 4 waves of data), we demonstrate the importance of the resource‐based pathway for expatriate assignments.